Method for preparing metal-cnt nanocomposite, water electrolysis catalyst electrode including metal-cnt nanocomposite prepared by the method, and method for preparing the water electrolysis catalyst electrode
Patent Information
- Application Number
- CN202280069225.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Priority Date
- 2021-10-14
- Filing Date
- 2022-10-11
- Publication Date
- 2026-10-30
- Estimated Expiration
- 2042-10-11
AI Technical Summary
[0006]为了减少电能成本,需要降低参与反应的过电压,因此不可避免地需要使用电极催化剂,但是合成电极催化剂的方法主要采用合成时间长且催化剂单价高贵的湿法,因而存在使氢气生产成本上升的缺点
[0027]本公开使用热等离子体制备可用作为水电解催化剂或锂离子电池电极材料的金属-CNT纳米复合材料,并制备包括该材料的水电解催化剂电极,从而在不使用湿法的情况下,因优异的过电位、电流密度和表面积而在阴极或阳极表现出优异的析氧反应(OER)和析氢反应(HER)。
Smart Images

Figure CN118159685B_ABST
Abstract
Description
Technical Field
[0001] Cross-references to related applications
[0002] This application claims priority to Korean Patent Application No. 2021-0136848, filed on October 14, 2021, the entire contents of which are incorporated herein by reference.
[0003] This disclosure relates to a method for preparing a metal-CNT nanocomposite material, including a water electrolysis catalyst electrode of the metal-CNT nanocomposite material prepared by the method, and a method for preparing the water electrolysis catalyst electrode. Background Technology
[0004] When electrical energy is applied to water molecules, hydrogen and oxygen molecules are produced. This reaction consists of two reactions: the hydrogen evolution reaction (HER) and the oxygen evolution reaction (OER).
[0005] Theoretically, water electrolysis should take place at 1.23V, but in practice, producing hydrogen and oxygen requires an overvoltage higher than that. Higher overvoltages produce more hydrogen and oxygen, but this also increases the cost of electricity.
[0006] To reduce electricity costs, it is necessary to lower the overvoltage involved in the reaction, which inevitably requires the use of electrode catalysts. However, the main method for synthesizing electrode catalysts is the wet process, which has a long synthesis time and high catalyst unit price, thus increasing the cost of hydrogen production.
[0007] Therefore, there is a need for electrode catalyst preparation technology that can solve the above problems.
[0008] Existing technical documents
[0009] Patent documents
[0010] 1. Korean Patent No. 10-1733492 (April 28, 2017). Summary of the Invention
[0011] Technical issues
[0012] The purpose of this disclosure is to provide a method for preparing metal-CNT (carbon nanotube) nanocomposites that can be used as water electrolysis catalysts or lithium-ion battery electrode materials without using existing wet processes, as well as a water electrolysis catalyst electrode including a metal-CNT nanocomposite material with excellent performance as a water electrolysis catalyst and its preparation method.
[0013] Technical solution
[0014] To address the aforementioned technical problems, this disclosure provides a method for preparing a metal-CNT nanocomposite material, comprising the following steps: injecting plasma-forming gas into a triple torch-type plasma jet device and generating a plasma jet by applying a power source; injecting metal and CNTs into the plasma jet using a carrier gas, causing the metal to vaporize and deposit onto the CNTs; and cooling the CNTs with deposited metal and recovering the metal-CNT nanocomposite material.
[0015] The molar ratio of the metal to CNT can be from 1:1 to 3:1.
[0016] The metal may be copper or nickel.
[0017] The diameter of the CNT can be from 1 nm to 30 nm, and the length can be less than or equal to 20 μm.
[0018] The metal can be injected together with argon gas at a rate of 3 L / min to 8 L / min, and the CNT can be injected together with argon gas at a rate of 5 L / min to 55 L / min.
[0019] The metal-CNT nanocomposite material can be in the form of the metal deposited on the surface of the CNT.
[0020] This disclosure also provides a metal-CNT nanocomposite material prepared by the above-described preparation method.
[0021] Another aspect of this disclosure provides a method for preparing a water electrolysis catalyst electrode comprising a metal-CNT nanocomposite material, comprising the following steps: preparing the metal-CNT nanocomposite material by the above method; and coating the metal-CNT nanocomposite material onto the water electrolysis catalyst electrode.
[0022] The step of coating the metal-CNT nanocomposite material onto the electrode of a water electrolysis catalyst may include the following steps: preparing a catalyst ink comprising the metal-CNT nanocomposite material; and coating the catalyst ink onto the electrode.
[0023] The steps for preparing the catalyst ink may include the following steps: mixing metal-CNT nanocomposite material, propanol, deionized water, and perfluorosulfonic acid membrane (Nafion) to prepare a mixture; and subjecting the mixture to ultrasonic treatment for 50 to 70 minutes.
[0024] The amount of metal-CNT nanocomposite material coated on the electrode can be from 1 mg to 1.5 mg per square centimeter of the electrode surface.
[0025] Another aspect of this disclosure provides a water electrolysis catalyst electrode comprising a metal-CNT nanocomposite material prepared by the aforementioned preparation method.
[0026] The effects of the invention
[0027] This disclosure uses thermal plasma to prepare metal-CNT nanocomposites that can be used as water electrolysis catalysts or lithium-ion battery electrode materials, and prepares water electrolysis catalyst electrodes including the material, thereby exhibiting excellent oxygen evolution reaction (OER) and hydrogen evolution reaction (HER) at the cathode or anode due to excellent overpotential, current density and surface area without the use of wet processes. Attached Figure Description
[0028] Figure 1 This is a diagram illustrating a triple torch-type plasma jet apparatus according to the present disclosure.
[0029] Figure 2 This is a flowchart illustrating a method for preparing metal-CNT nanocomposites according to the present disclosure.
[0030] Figure 3 This is a flowchart illustrating a method for preparing a water electrolysis catalyst electrode according to the present disclosure.
[0031] Figure 4 This is a flowchart illustrating the steps for preparing the catalyst ink according to the present disclosure.
[0032] Figure 5 The image shows the XRD (x-ray diffraction) charts of the nickel-CNT nanocomposites prepared in Preparation Examples 1 to 3 and recovered from the first reactor.
[0033] Figure 6 The image shows the XRD pattern of the nickel-CNT nanocomposite material prepared in Preparation Example 2 and recovered from reactors 1 to 3.
[0034] Figure 7 The graph shows the FE-SEM (field emission scanning electron microscopy) results of the nickel-CNT nanocomposites prepared in Preparation Examples 1 to 3 and recovered from the first reactor.
[0035] Figure 8 The results of FE-TEM, SEAD (selected region electron diffraction), and EDS analyses of the nickel-CNT nanocomposite material prepared in Preparation Example 2 and recovered from the first reactor are shown.
[0036] Figure 9 XRD patterns of copper-CNT nanocomposites prepared in Preparation Examples 4 to 6 and recovered from Reactor 1 are shown.
[0037] Figure 10XRD patterns of copper-CNT nanocomposites prepared in Preparation Example 5 and recovered from reactors 1 to 3 are shown.
[0038] Figure 11 The graph shows the FE-SEM results of the copper-CNT nanocomposites recovered from the first reactor in Preparation Examples 1 to 3.
[0039] Figure 12 The results of FE-TEM, SEAD, and EDS analyses of the nickel-CNT nanocomposite material recovered from reactor 1 in Preparation Example 5 are shown.
[0040] Figure 13 This is a diagram showing a Potentiostat / Galva-nostat (PGSTAT128N, Metrohm, Switzerland) consisting of three electrodes.
[0041] Figure 14a This is a graph showing the linear sweep voltammetry (LSV) of the OER reaction.
[0042] Figure 14b This is a graph showing the overvoltage measurements based on LSV measurements.
[0043] Figure 14c This is a graph showing the Tafel slope.
[0044] Figure 15a This is a graph showing the results of cyclic voltammetry (CV) measurements at the scan rate according to Example 4 (Cu-CNT) in the OER reaction.
[0045] Figure 15b This is a graph showing the results of cyclic voltammetry (CV) measurements at the scan rate according to Example 2 (Ni-CNT) in the OER reaction.
[0046] Figure 15c This is a graph showing the difference in current density between the highest and lowest points of the center voltage position in the OER reaction, measured on a CV measurement data graph, and the variation of the current density difference with the scan rate.
[0047] Figure 16a This is a graph showing the linear sweep voltammetry (LSV) plot of the HER response.
[0048] Figure 16b This is a graph showing the overvoltage measurements based on LSV measurements.
[0049] Figure 16cThis is a graph showing the Tafel slope.
[0050] Figure 17a A graph showing the results of cyclic voltammetry (CV) measurements at the scan rate according to Example 4 (Cu-CNT) in the HER reaction is presented.
[0051] Figure 17b This is a graph showing the results of cyclic voltammetry (CV) measurements at the scan rate according to Example 2 (Ni-CNT) in the HER reaction.
[0052] Figure 17c In the HER reaction, the difference in current density between the highest and lowest points of the center voltage position in the CV measurement data graph is measured, thus showing a graph of the difference in current density as it changes with the scan rate. Detailed Implementation
[0053] The preferred embodiments of this disclosure are described in detail below. In this disclosure, detailed descriptions of related known technologies will be omitted when they are deemed to obscure the main points of the disclosure. Throughout the specification, when a portion is described as "comprising" certain constituent elements, it means that the constituent elements may be included, rather than excluding other constituent elements, unless otherwise stated.
[0054] Before describing this disclosure, the triple torch plasma device used in this disclosure will be described first.
[0055] Figure 1 This is a diagram illustrating a triple torch-type plasma jet apparatus according to the present disclosure.
[0056] refer to Figure 1 The triple torch-type plasma jet device includes: a reaction tube 100, which provides a space for forming a plasma jet and in which the raw material reacts; a torch section 200, which is disposed on one side of the reaction tube 100 to provide a heat source to the supplied initial material; a metal supply section 300, which is connected to the upper part of the reaction tube 100 to supply metal raw material into the reaction tube 100 through a pipeline; a CNT supply section 400, which is connected to the central part of the reaction tube 100 to supply CNT raw material into the reaction tube 100 through a pipeline; a power supply device 500, which is electrically connected to the torch section 200 to provide power; and a gas supply device 600, which is connected to the torch section 200, the metal supply section 300 and the CNT supply section 400 to supply gas, wherein multiple torches are arranged at equal intervals in the torch section 200 so that the plasma jets generated from the multiple torch sections 200 can be merged.
[0057] Furthermore, the metal is supplied in the same direction as the plasma jet of the flare section 200, and the CNT is supplied from the center of the reaction tube 100 in the opposite direction to the plasma jet.
[0058] When the CNTs (carbon nanotubes) are injected along with a large amount of carrier gas, some of them sublimate due to the high temperature of the plasma jet and therefore cannot exist in the form of CNTs when they are supplied together with the metal. Therefore, as mentioned above, it is preferable to supply the CNTs and metal separately and inject them together with a large amount of carrier gas.
[0059] The reaction tube 100 is a space in which raw materials react due to a plasma jet and prepared materials are deposited therein. It may include a first reactor 110, a second reactor 120 and a third reactor equipped with a quenching system on one side.
[0060] The flare section 200 may be equipped with three flares arranged at equal intervals.
[0061] The generation of the triple torch-type plasma jet used in this disclosure is preferably performed in a non-transferred manner.
[0062] In this disclosure, a triple torch-type plasma jet device generates a DC arc discharge between a cathode made of a tungsten rod and an anode on the inner surface of a nozzle made of copper. Plasma-forming gas is fed into a vortex flow from the rear, thereby heating the plasma-forming gas through the arc. By generating a non-transfer plasma jet that ejects a violent plasma jet from the anode nozzle, metal-CNT nanocomposite materials can be prepared.
[0063] The plasma jet is an ionized gas composed of electrons, ions, atoms, and molecules generated in the flare section using a DC electric arc or high-frequency inductive coupling discharge. It is an ultra-high temperature and highly active high-speed jet with temperatures ranging from thousands to tens of thousands of Kelvin (K).
[0064] The preparation method of metal-CNT nanocomposite material will now be described in detail as one embodiment of this disclosure.
[0065] like Figure 2 As shown, the metal-CNT nanocomposite material according to this disclosure can be prepared by the following steps: injecting plasma forming gas into a triple torch-type plasma jet device and generating a plasma jet by applying a power source; injecting metal and CNT into the plasma jet respectively using a carrier gas, causing the metal to vaporize and deposit onto the CNT; and cooling the CNT with deposited metal and recovering the metal-CNT nanocomposite material.
[0066] The steps of injecting plasma-forming gas into a triple torch plasma jet apparatus and generating a plasma jet by applying a power supply can be performed as follows: After mixing argon (Ar) and nitrogen (N2), inject the mixture into the triple torch plasma jet apparatus at a flow rate of 8 L / min to 16 L / min, and adjust the plasma input power to 18 kW to 25 kW. At this time, argon and nitrogen can be mixed at flow rates of 2 L / min to 6 L / min and 6 L / min to 10 L / min, respectively.
[0067] The steps of injecting metal and CNT into the plasma jet using a carrier gas, and then vaporizing the metal and depositing it onto the CNT are performed as follows.
[0068] First, the metal raw material and CNTs are injected together with a carrier gas. At this point, the metal raw material and CNTs can be injected in opposite directions, and the carrier gas can be argon.
[0069] The flow rate of argon gas injected along with the metal raw material can be from 2 L / min to 7 L / min, and the amount of metal raw material added can be from 0.5 g / min to 0.7 g / min. Alternatively, the flow rate of argon gas injected along with the CNT raw material can be from 5 L / min to 55 L / min, preferably from 20 L / min to 40 L / min, more preferably from 25 L / min to 30 L / min, and the amount of CNT raw material added can be from 0.05 g / min to 0.07 g / min.
[0070] The optimal water electrolysis catalyst performance is observed within the ranges of metal and CNT input amounts and the argon flow rate, therefore these ranges are preferred.
[0071] Furthermore, if the argon flow rate injected along with the CNT is less than 5 L / min or greater than 55 L / min, the metal may not be deposited on the CNT surface, resulting in the synthesis of ordinary nano-sized metal particles.
[0072] The injected metal material is vaporized by the plasma jet and deposited on the surface of the CNTs, thereby forming a metal-CNT nanocomposite material. Since the CNTs and the metal are introduced separately and therefore not vaporized, the metal can be deposited on the CNT surface.
[0073] To cool the metal-deposited CNTs, cooling systems may be further provided in the first reactor 110, the second reactor 120, and the third reactor 130. The cooling may be natural cooling, and the metal-CNT nanocomposite material is produced as the metal-deposited CNTs are cooled.
[0074] The molar ratio of the added metal to CNTs can be from 1:1 to 3:1, preferably 2:1. Within this range, metal-CNT nanocomposites can be easily formed.
[0075] The metal may be copper or nickel powder with a diameter of 0.5 μm to 2 μm, preferably nickel powder.
[0076] The metal-CNT nanocomposite material prepared by the process is prepared in a short time by a single STEP, thus improving energy efficiency, and the metal-CNT nanocomposite material can be in the form of the metal deposited on the CNT surface.
[0077] Another embodiment of this disclosure relates to a metal-CNT nanocomposite material prepared by the above-described preparation method.
[0078] The metal-CNT nanocomposite material can be used in various fields, and is preferably used as a cathode material for lithium-ion batteries or a water electrolysis catalyst.
[0079] According to another embodiment of this disclosure, there is a method for preparing a water electrolysis catalyst electrode, the water electrolysis catalyst electrode comprising a metal-CNT nanocomposite material prepared by the above preparation method.
[0080] like Figure 3 As shown, the water electrolysis catalyst electrode according to this disclosure can be prepared by the following steps: preparing a metal-CNT nanocomposite material using the above preparation method; and coating the metal-CNT nanocomposite material onto the water electrolysis catalyst electrode.
[0081] The preparation method of metal-CNT nanocomposites is as described above, therefore detailed description is omitted.
[0082] According to another embodiment of this disclosure, there is a method for preparing a catalyst ink, the catalyst ink comprising a metal-CNT nanocomposite material prepared by the above-described preparation method.
[0083] like Figure 4 As shown, the preparation steps of the catalyst ink including metal-CNT nanocomposite material include the following steps: mixing metal-CNT nanocomposite material, propanol, deionized water, and perfluorosulfonic acid membrane (Nafion) to prepare a mixture; and subjecting the mixture to ultrasonic treatment for 50 to 70 minutes.
[0084] The mixture can be prepared by mixing 40 mg to 60 mg of metal-CNT nanocomposite material, 600 μl to 800 μl of propanol, 200 μl to 400 μl of deionized water, and 5 μl to 20 μl of perfluorosulfonic acid membrane (5 wt%).
[0085] If the ultrasonic treatment time exceeds the specified range, the preparation efficiency of the catalyst ink decreases, therefore the specified range is preferred.
[0086] The step of coating the catalyst ink onto the electrode can be performed by applying the ultrasonically treated catalyst ink onto the electrode and then drying it. Specifically, 2 μl to 5 μl of the ultrasonically treated catalyst ink can be applied to the electrode using a pipette and then dried at room temperature for 40 to 50 minutes.
[0087] The electrode can be a glassy carbon electrode, and the amount of metal-CNT nanocomposite material coated on the electrode can be 1 mg to 1.5 mg per square centimeter of the electrode surface, preferably 1.2 mg per square centimeter of the electrode surface.
[0088] When the amount of metal-CNT nanocomposite material coated on the electrode surface exceeds the specified range, cracks appear after the coated ink dries, and it becomes difficult to coat the electrode. Therefore, the specified range is preferred.
[0089] As an implementation of this disclosure, this disclosure provides a water electrolysis catalyst electrode, which includes a metal-CNT nanocomposite material prepared by the preparation method described above.
[0090] According to the present disclosure, the water electrolysis catalyst electrode can generate hydrogen and oxygen at the cathode or anode, respectively. Specifically, it can exhibit excellent hydrogen evolution reaction or oxygen evolution reaction at the cathode or anode of alkaline electrolyte (1M KOH), respectively.
[0091] The present disclosure will be further explained below with reference to embodiments and experimental examples.
[0092] Preparation Examples 1 to 3: Nickel-CNT Nanocomposites
[0093] Towards Figure 1 The flare section of the triple torch-type plasma jet device shown supplies plasma-forming gas and generates a plasma jet according to the operating conditions in Table 1 below.
[0094] Subsequently, nickel and CNTs were supplied to the triple torch-type plasma jet device, and the nickel was vaporized and deposited on the surface of the CNTs.
[0095] Subsequently, the nickel-deposited CNTs were cooled to prepare a nickel-CNT nanocomposite material with nickel deposited on the CNT surface.
[0096] Here, commercially available nickel (1 μm, 99.8% purity, Sigma-Aldrich, USA) and CNTs (diameter: 5 nm to 20 nm, length: less than or equal to 10 μm, Carbon Nano-materia Technology, Korea) were used, and the operation time was 10 minutes.
[0097] Table 1
[0098]
[0099] Preparation Examples 4 to 6: Copper-CNT Nanocomposites
[0100] Towards Figure 1 The flare section of the triple torch-type plasma jet device shown supplies plasma-forming gas and generates a plasma jet according to the operating conditions in Table 2 below.
[0101] Subsequently, copper and CNTs were supplied to the triple torch-type plasma jet device, and the copper was vaporized and deposited on the surface of the CNTs.
[0102] Subsequently, copper-CNT nanocomposites were prepared by cooling the CNTs with copper deposited on their surface.
[0103] Here, commercially available copper (1μm, 99.5% purity, Sigma-Aldrich, USA) and CNTs (diameter: 5~20nm, length: less than or equal to 10μm, carbon nanomaterials, technology from South Korea) were used, and the operation time was 10 minutes.
[0104] Table 2
[0105]
[0106] Example 1
[0107] The catalyst ink was prepared by mixing 50 mg of nickel-CNT nanocomposite material prepared by Example 1, 700 μl of propanol, 300 μl of deionized water and 10 μl of perfluorosulfonic acid membrane (5 wt%), and then subjecting the mixture to ultrasonic treatment for 60 minutes.
[0108] The prepared catalyst ink was loaded (coated) onto a pre-cleaned glassy carbon electrode at a rate of 1.2 mg per square centimeter using a pipette, and then dried in air for 50 minutes to prepare the catalyst electrode.
[0109] Example 2
[0110] The catalyst ink was prepared by mixing 50 mg of nickel-CNT nanocomposite material prepared in Example 2, 700 μl of propanol, 300 μl of deionized water and 10 μl of perfluorosulfonic acid membrane (5 wt%), and then subjecting the mixture to ultrasonic treatment for 60 minutes.
[0111] The prepared catalyst ink was loaded (coated) onto a pre-cleaned glassy carbon electrode at a rate of 1.2 mg per square centimeter using a pipette, and then dried in air for 50 minutes to prepare the catalyst electrode.
[0112] Example 3
[0113] The catalyst ink was prepared by mixing 50 mg of copper-CNT nanocomposite material prepared in Example 4, 700 μl of propanol, 300 μl of deionized water and 10 μl of perfluorosulfonic acid membrane (5 wt%), and then subjecting the mixture to ultrasonic treatment for 60 minutes.
[0114] The prepared catalyst ink was loaded (coated) onto a pre-cleaned glassy carbon electrode at a rate of 1.2 mg per square centimeter using a pipette, and then dried in air for 50 minutes to prepare the catalyst electrode.
[0115] Example 4
[0116] The catalyst ink was prepared by mixing 50 mg of copper-CNT nanocomposite material prepared in Example 5, 700 μl of propanol, 300 μl of deionized water and 10 μl of perfluorosulfonic acid membrane (5 wt%), and then subjecting the mixture to ultrasonic treatment for 60 minutes.
[0117] The prepared catalyst ink was loaded (coated) onto a pre-cleaned glassy carbon electrode at a rate of 1.2 mg per square centimeter using a pipette, and then dried in air for 50 minutes to prepare the catalyst electrode.
[0118] Experimental Example 1
[0119] The crystal structure of the nickel-CNT nanocomposites prepared in Examples 1 to 3 was analyzed by X-ray diffraction, and the crystal structure was analyzed by FE-SEM. The results are shown below. Figures 5 to 7 middle.
[0120] Figure 5 The following are XRD patterns of the nickel-CNT nanocomposites prepared in Preparation Examples 1 to 3 and recovered from the first reactor. Figure 6 This shows the XRD patterns of the nickel-CNT nanocomposites prepared in Preparation Example 2 and recovered from reactors 1 to 3. Figure 7 The graph shows the FE-SEM results of the nickel-CNT nanocomposites prepared in Preparation Examples 1 to 3 and recovered from the first reactor.
[0121] Reference Figure 5 Two peaks were observed for Ni and CNT, but CNT has much lower crystallinity than Ni, so the CNT peak is shown in the graph. Furthermore, it can be confirmed that because CNT was introduced with a large amount of argon gas while separated from the metal, its structure remained intact even when exposed to the high temperature of the plasma, thus preventing the formation of nickel carbide due to the absence of C reacting with Ni.
[0122] Reference Figure 6 Based on the location of the trapping, only Ni peaks are present, and the crystallinity also exhibits similar characteristics.
[0123] Reference Figure 7 It can be confirmed that in preparation examples 1 (a, b), the morphology present is not that of Ni-CNT nanocomposite material, but rather that of ordinary spherical nanoparticles, thus confirming the synthesis of Ni nanoparticles. In preparation examples 2 (c, d) and 3 (e, f), it can be confirmed that the morphology of particles presumed to be Ni (nickel) attached to the CNT surface is observed.
[0124] Experiment Example 2
[0125] The nickel-CNT nanocomposite material prepared in Preparation Example 2 and recovered from Reactor 1 was analyzed using FE-TEM (Talos Fe200X G2, Thermo Fisher Scientific, US), SEAD, and EDS. The results are shown in [Table / Information missing]. Figure 8 middle.
[0126] Figure 8 The results are FE-TEM, SEAD, and EDS analyses of the nickel-CNT nanocomposite material prepared in Preparation Example 2 and recovered from Reactor 1.
[0127] Reference Figure 8 The FE-TEM image (a) confirms that particles are deposited on the CNT surface, and the SAED mode (b) confirms that it exhibits the same data as the XRD diffraction analysis. Furthermore, TEM-EDS mapping analysis (c to f) confirms that the particles deposited on the CNT surface are Ni, and that a thin oxide film encapsulates the particles.
[0128] Experimental Example 3
[0129] The crystal structure of the copper-CNT nanocomposites prepared in Preparation Examples 4 to 6 was analyzed using X-ray diffraction or FE-SEM. The results of the FE-SEM analysis are shown below. Figures 9 to 11 middle.
[0130] Figure 9 These are XRD patterns of the copper-CNT nanocomposites prepared in Examples 4 to 6 and recovered from Reactor 1. Figure 10 These are XRD patterns of the copper-CNT nanocomposites prepared in Preparation Example 5 and recovered from reactors 1 to 3. Figure 11 The results are FE-SEM images of the copper (Cu)-CNT nanocomposites prepared in Examples 1 to 3 and recovered from the first reactor.
[0131] Reference Figure 9 Two peaks were observed for Cu and CNT, but CNT has relatively lower crystallinity than Cu, so the CNT peak is not obvious on the graph. Furthermore, it was found that because CNT was introduced with a large amount of argon gas while separated from the metal, even when exposed to the high temperature of the plasma, the CNT did not undergo structural deformation and was preserved. Therefore, copper carbide was not synthesized due to the absence of C reacting with Cu.
[0132] Reference Figure 10 Based on the location of the trapping, only Cu peaks are present, and the crystallinity also exhibits similar characteristics.
[0133] Reference Figure 11 It can be confirmed that in preparation examples 4 (a, b), the morphology present is not that of Cu-CNT nanocomposite material, but rather that of ordinary spherical nanoparticles, thus confirming the synthesis of Ni nanoparticles. In preparation examples 5 (c, d) and 6 (e, f), it can be confirmed that the morphology is that of Ni particles attached to the CNT surface, and the particle size is relatively large compared to Ni-CNT nanocomposite material.
[0134] This is due to the difference in thermal conductivity between Ni and Cu. Since Cu, which has higher thermal conductivity, forms nuclei faster than Ni, the growth time is longer, resulting in larger particles than Ni-CNT.
[0135] Experiment Example 4
[0136] The copper-CNT nanocomposite material prepared in Preparation Example 5 and recovered from Reactor 1 was analyzed using FE-TEM (Talos Fe200X G2 (Thermo Fisher Scientific, US)), SEAD, and EDS, and the results are shown below. Figure 12 middle.
[0137] Figure 12 The results are FE-TEM, SEAD, and EDS analyses of the nickel-CNT nanocomposite material prepared in Preparation Example 5 and recovered from Reactor 1.
[0138] Reference Figure 12As can be seen from the FE-TEM image (a), the particles are deposited on the CNT surface, and the SAED mode (b) shows the same data as the XRD diffraction analysis. In addition, TEM-EDS mapping analysis (c to f) confirms that the particles deposited on the CNT surface are Cu, and a thin oxide film is formed to encapsulate the particles.
[0139] Experimental Example 5
[0140] Electrochemical property evaluation methods
[0141] The electrochemical properties of the water electrolysis catalysts prepared in Examples 1 to 4 were evaluated using a Potentiostat / alva-nostat (PGSTAT128N, Metrohm, Switzerland) consisting of three electrodes. The equipment used is shown in [the table / image / image]. Figure 13 middle.
[0142] A glassy carbon electrode with a diameter of 3 mm was used as the working electrode, a platinum sheet was used as the counter electrode, and Ag / AgCl / 3M KCl with a double junction was used as the reference electrode.
[0143] In this disclosure, all potentials are calculated based on a reversible hydrogen electrode (RHE) using the following formula 1.
[0144] Mathematical Formula 1
[0145] ERHE=EAg / AgCl+0.1976 V+(0.059×pH))
[0146] In this disclosure, all electrochemical electrolytes used were 1M KOH (pH 14), and all solutions used a vortexer that rotated the working electrode at 1600 rpm to remove bubbles generated on the working electrode.
[0147] For the oxygen evolution reaction (OER), linear sweep voltammetry (LSV) was performed at a scan rate of 10 mV / s in the range of 0.5 V vs to 2 V vs. RHE.
[0148] The double-layer capacitance (Cdl) used to obtain the electrochemical active surface area (ECSA) was measured in a voltage range of 1.1 V vs to 1.4 V vs. RHE when the induced current was not flowing. The voltage-current (CV) plot was measured by changing the scan rate from 20 mV / s to 120 mV / s, and the CV plot was used for measurement.
[0149] For the hydrogen evolution reaction (HER), linear sweep voltammetry (LSV) was performed at a scan rate of 10 mV / s in the range of 0 V vs to -1 V vs. RHE.
[0150] The electric double-layer capacitance (Cdl) used to obtain the electrochemical active surface area (ECSA) is measured in a voltage range of 0.4 Vvs to 0.6 VvsRHE where the induced current does not flow. The voltage-current (CV) plot is measured by changing the scan rate from 20 mV / s to 120 mV / s, and the CV plot is then used to calculate the capacitance.
[0151] Results and Analysis
[0152] 1. Oxygen Evolution Reaction
[0153] 1-1. Analysis of the reactivity of oxygen formation
[0154] Figure 14a This is a linear sweep voltammetry (LSV) plot of the OER reaction. Figure 14b It is a graph displaying overvoltage measurements based on LSV measurements. Figure 14c It is a graph showing the Tafel slope.
[0155] refer to Figure 14a It can be confirmed that, compared with Cu-CNT nanocomposites (Examples 3 and 4), the current increases sharply with the increase of voltage when Ni-CNT nanocomposites (Examples 1 and 2) are included.
[0156] Furthermore, a higher current density was observed at an argon flow rate of 27 L / min (Examples 2 and 4) compared to an argon flow rate of 10 L / min (Examples 1 and 3). This is because at lower argon flow rates, ordinary spherical nanoparticles are formed, while at higher flow rates, metal is deposited on the CNT surface.
[0157] Reference Figure 14bIt can be confirmed that the overvoltage values exhibited by the Ni-CNT nanocomposite materials (Examples 1 and 2) are lower than those exhibited by the Cu-CNT nanocomposite materials (Examples 3 and 4).
[0158] Specifically, it can be confirmed that at 10 mA / cm 2 and 20mA / cm 2 Example 2 uses 0.328V and 0.350V, which is lower than Example 4.
[0159] Reference Figure 14c It can be confirmed that the Tafel slope of Example 2 (Ni-CNT) is 62.4 mV / dec, which is lower than that of Example 4 (Ni-CNT) at 66.5 mV / dec.
[0160] The results confirm that, according to Example 2, when argon gas is introduced at a flow rate of 27 L / min and includes Ni-CNT nanocomposite material, the reaction with oxygen evolution is excellent.
[0161] Electrochemical active surface area (ECSA) analysis
[0162] Figure 15a This is a graph showing the results of cyclic voltammetry (CV) measurements at the scan rate according to Example 4 (Cu-CNT) in the OER reaction. Figure 15b This is a graph showing the results of cyclic voltammetry (CV) measurements at the scan rate according to Example 2 (Ni-CNT) in the OER reaction. Figure 15c This is a graph showing the difference in current density between the highest and lowest points of the center voltage position in the OER reaction, measured by CV test data, and the change in current density difference according to the scan rate.
[0163] Figure 15c The slope of the curve implies that the greater the slope, which is proportional to the double-layer capacitance (Cdl) value, the larger the active surface area of the catalyst. (This is achieved through...) Figures 15a to 15c It can be confirmed that the surface activity of Example 2 (Ni-CNT) is higher than that of Example 4 (Cu-CNT).
[0164] The results show that when argon gas is introduced at a flow rate of 27 L / min according to the embodiments, and the Ni-CNT nanocomposite material is included, the oxygen evolution reaction is excellent.
[0165] 2. Hydrogen evolution reaction
[0166] 2-1. Hydrogen Reactivity Analysis
[0167] Figure 16a This is a graph showing the linear sweep voltammetry (LSV) curves of the HER response. Figure 16bThis shows the overvoltage measurement value based on the LSV measurement results. Figure 16c This is a graph showing the Tafel slope.
[0168] Reference Figure 16a It can be confirmed that, compared with the case including Ni-CNT nanocomposites (Examples 1 and 2), the current including Cu-CNT nanocomposites (Examples 3 and 4) increases sharply with the increase of voltage.
[0169] Furthermore, a higher current density was observed at an argon flow rate of 27 L / min (Examples 2 and 4) compared to an argon flow rate of 10 L / min (Examples 1 and 3).
[0170] Reference Figure 16b It can be seen that the overvoltage value of the Ni-CNT nanocomposite material (Examples 1 and 2) is lower than that of the Cu-CNT nanocomposite material (Examples 3 and 4).
[0171] Specifically, at 10 mA / cm 2 and 20mA / cm 2 In this study, Example 2 (Ni-CNT) exhibited -0.192V and -0.228V, while Example 4 (Cu-CNT) showed a voltage of 10mA / cm. 2 The measured value was -0.439V at 20mA / cm. 2 The measurement was -0.490V.
[0172] Reference Figure 16c As can be seen, the Tafel slope of Example 2 (Ni-CNT) is 48.8 mV / dec, which is lower than that of Example 4 (Ni-CNT) at 98.2 mV / dec.
[0173] The results show that when argon gas is introduced at a flow rate of 27 L / min according to Example 2, and the mixture contains Ni-CNT nanocomposite material, it exhibits excellent performance in hydrogen evolution reaction.
[0174] 2-2. Electrochemical Active Surface Area (ECSA) Analysis
[0175] Figure 17a This is a graph showing the results of cyclic voltammetry (CV) measurements at the scan rate according to Example 4 (Cu-CNT) in the HER reaction. Figure 17b This is a graph showing the results of cyclic voltammetry (CV) measurements at the scan rate according to Example 2 (Ni-CNT) in the HER reaction. Figure 17c It measures the difference in current density between the highest and lowest points of the center voltage position in the CV test data plot during the HER reaction, thus showing a graph of the difference in current density as it changes with the scan rate.
[0176] Figure 17c The slope of the curve implies that the greater the slope, which is proportional to the double-layer capacitance (Cdl), the larger the active surface area of the catalyst. (Reference) Figures 17a to 17c It can be seen that the surface activity of Example 2 (Ni-CNT) is higher than that of Example 4 (Cu-CNT).
[0177] The results show that when argon gas is introduced at a flow rate of 27 L / min according to Example 2, and the Ni-CNT nanocomposite material is included, the hydrogen evolution reaction is excellent.
[0178] Experimental Example 5: Comparison of the activity of various catalysts in similar electrolytes
[0179] Table 3 below compares the activity of catalysts prepared by chemical reduction and non-electrolytic plating methods, as well as the water electrolysis catalyst including the metal-CNT catalyst of this disclosure, on OER and HER under the same electrolyte or pH conditions.
[0180] Table 3
[0181]
[0182] NP: Nanoparticles, NS: Nanosheets, NR: Nanorods, NB: Nanoribbons, 3D NNCNTAs: Three-dimensional Ni@[Ni(2+ / 3+)Co2(OH)] 6-7 x nanotube array, NF: nickel foam
[0183] Most existing catalysts require chemical reduction methods involving multiple steps and long processing times to synthesize, while the process using thermal plasma in this disclosure eliminates the need for redundant processes such as filtration and drying.
[0184] In particular, it can be confirmed that the OER and HER activities of the Ni-CNT nanocomposite material disclosed herein are excellent compared with cobalt-based catalysts such as Co2B-500, Co-Ni NP / NS, and CoB / NF.
[0185] As described above, this disclosure uses thermal plasma to prepare metal-CNT nanocomposites that can be used as water electrolysis catalysts or lithium-ion battery electrode materials, and prepares water electrolysis catalyst electrodes including the material, thereby exhibiting excellent oxygen evolution reaction (OER) and hydrogen evolution reaction (HER) at the cathode or anode due to excellent overpotential, current density and surface area without using a wet method.
[0186] The preferred embodiments of this disclosure have been described in detail above, but the scope of this disclosure is not limited thereto. Various modifications and improvements made by those skilled in the art based on the basic concepts of this disclosure as defined in the appended claims are also included within the scope of this disclosure.
[0187] Figure Labels
[0188] 100: Reaction tube 110: First reaction tube
[0189] 120: Second reaction tube; 130: Third reaction tube
[0190] 200: Torch Department; 300: Metal Supply Department
[0191] 400: CNT Supply Department; 500: Power Supply Unit
[0192] 600: Gas supply unit
[0193] Industrial availability
[0194] According to the preparation method of the metal-CNT nanocomposite material disclosed herein, a metal-CNT nanocomposite material that can be used as a water electrolysis catalyst or a lithium-ion battery electrode material is prepared using thermal plasma, and a water electrolysis catalyst electrode including the material is prepared, thereby exhibiting excellent oxygen evolution reaction (OER) and hydrogen evolution reaction (HER) at the cathode or anode due to its excellent overpotential, current density and surface area without the use of wet process.
Claims
1. A method for preparing a water electrolysis catalyst electrode comprising a metal-CNT nanocomposite material, comprising the following steps: Preparation of the metal-CNT nanocomposite material; and The metal-CNT nanocomposite material was coated onto the electrode of the water electrolysis catalyst. The steps for preparing the metal-CNT nanocomposite material include the following steps: Plasma-forming gas is injected into a triple torch-type plasma jet device, and a plasma jet is generated by applying a power source. Metal and CNTs are injected into the plasma jet using a carrier gas, causing the metal to vaporize and deposit on the CNTs; and The CNTs with deposited vaporized metal were cooled, and the metal-CNT nanocomposite material was recovered. The step of coating the metal-CNT nanocomposite material onto the water electrolysis catalyst electrode includes the following steps: Preparation of catalyst ink comprising the metal-CNT nanocomposite material; and The catalyst ink is coated onto the electrode. The steps for preparing the catalyst ink include the following steps: The metal-CNT nanocomposite material, propanol, deionized water, and perfluorosulfonic acid membrane were mixed to prepare a mixture; and The mixture is subjected to ultrasonic treatment for 50 to 70 minutes.
2. The method for preparing a water electrolysis catalyst electrode comprising a metal-CNT nanocomposite material according to claim 1, wherein, The amount of metal-CNT nanocomposite material coated on the electrode is 1 mg to 1.5 mg per square centimeter of the electrode surface.
3. A water electrolysis catalyst electrode, comprising: Metal-CNT nanocomposite material prepared by the preparation method according to claim 1.
Citation Information
Patent Citations
Thermal spray feedstock composition
US20060213326A1
